Character Strengths in the Life Domains of Work, Education, Leisure, and Relationships and Their Associations With Flourishing - Wagner, Lisa; Pindeus, Lisa; Ruch, Willibald (Frontiers in Psychology, 2021)
A growing body of research demonstrates the relevance of character strengths for flourishing in general, but also for important outcomes across different life domains (e.g., work performance, relationship satisfaction). Studies have also shown that there are differences in the extent to which character strengths are applied, that is, perceived as relevant and shown in behavior in a given context, between work and private life, but did not consider other life domains. This study aimed to close this gap by studying the life domains of work, education, leisure, close personal relationships, and romantic relationships. The present study investigated whether (a) strengths-related behavior across different life domains explains additional variance in flourishing beyond the trait-level of the respective character strength, and studies (b) differences in the relevance of character strengths and strengths-related behavior across different life domains and (c) their relationships with flourishing. A sample of 203 German-speaking adults (78.8% females; mean age = 29.4 years) completed self-reports assessing flourishing, character strengths, separately for all life domains they considered relevant (i.e., M = 4.23 life domains), the character strengths’ perceived relevance and the display of strengths-related behavior. The results demonstrate that (a) strengths-related behavior averaged across all relevant life domains explained unique variance in flourishing above the trait-level of character strengths in some cases (e.g., creativity, kindness, fairness), (b) different life domains were characterized by specific character strengths profiles – both regarding their relevance and strength-related behavior. Moreover, (c) character strengths and strengths-related behavior in different life domains both showed substantial correlations with flourishing. In some cases, these associations were domain-specific (e.g., love of learning – education). In conclusion, we suggest that examining strengths-related behavior across different life domains represents a worthwhile addition to research on character strengths.